OBSTACLES TO THE APPLICATION OF TOTAL QUALITY MANAGEMENT FOR TEACHERS OF SOME FACULTIES OF PHYSICAL EDUCATION AND SPORTS SCIENCES (ResearchJet Journal of Analysis and Inventions, 2022)
This research aimed to reveal the obstacles to the application of total quality management in some colleges of physical education and sports sciences in Iraq from the point of view of the research sample and to reveal ways to overcome these obstacles by answering the question What are the most important obstacles in the application of total quality management in some colleges Physical education and sports sciences in Iraq from the point of view of the research sample. To answer this question, the researchers built a scale consisting of (34) phrases that include obstacles related to the administrative body, obstacles related to the teaching staff, obstacles related to the university facility, obstacles related to scientific research, obstacles related to community service .